DESEMPENHO DE VACAS E BEZERROS DE CORTE NO PANTANAL SUPLEMENTADAS COM MISTURA MINERAL UREADA - CASTRO, Micheline Feitosa,; HERNANDES, Maria Simara Palermo,; SILVA, Andressa Rayane,; SILVA, Millena Vitória,; VEDOVATTO, Marcelo,; OLIVEIRA, Dalton Mendes, (ANAIS DO ENIC, 2023)
-